Post-Embryonic Development in Zaprionus indianus (Diptera: Drosophilidae) - Matavelli, Cristiane [UNESP]; Zara, Fernando José [UNESP]; Von Zuben, Claudio José [UNESP] (Entomological Soc Amer, 2013)
The objectives of this study were to determine the number of instars of Zaprionus indianus Gupta, 1970, a fly that is considered a pest on fig plantations; analyze the pupation process; and characterize the morphology of the immature stages. This information would fill a gap in the knowledge regarding Z. indianus development. The post-embryonic development of this species was studied by using Dyar's rule to characterize the immature stages of the fly. In addition, the morphological structures were analyzed by scanning electron microscopy. Following Dyar's rule, Z. indianus exhibited three larval instars. Pupae were formed in higher numbers during the morning, and 5 d was the average time until adult emergence. The male: female sex ratio in this population was 1: 1, with a higher emergence of females during the first 72 h. During the morphological analysis, the following structures were observed: (egg) chorionic cells, respiratory filaments, and micropyle; (larvae) body segments, intersegmental spines, antennae, the maxillary palp complex, sensilla, tubercles, and anterior and posterior spiracles; and (pupae) filaments that originated in the anterior spiracles and the presence of spines along these filaments. Some of these characteristics were slightly different from those observed in other drosophilids, which provides a taxonomic quality to these characteristics. In addition, these results may facilitate future studies on the biology, ecology, and control of this species.
Keywords: larval morphology; Dyar's rule; immature stage; pupation process; scanning electron microscopy